SWI/SNF inactivation in the endometrial epithelium leads to loss of epithelial integrity. (19th October 2020) - Reske, Jake J; Wilson, Mike R; Holladay, Jeanne; Wegener, Marc; Adams, Marie; Chandler, Ronald L
Abstract: Although ARID1A mutations are a hallmark feature, mutations in other SWI/SNF (SWItch/Sucrose Non-Fermentable) chromatin remodeling subunits are also observed in endometrial neoplasms. Here, we interrogated the roles of Brahma/SWI2-related gene 1 (BRG1, SMARCA4), the SWI/SNF catalytic subunit, in the endometrial epithelium. BRG1 loss affects more than one-third of all active genes and highly overlaps with the ARID1A gene regulatory network. Chromatin immunoprecipitation studies revealed widespread subunit-specific differences in transcriptional regulation, as BRG1 promoter interactions are associated with gene activation, while ARID1A binding is associated with gene repression. However, we identified a physiologically relevant subset of BRG1 and ARID1A co-regulated epithelial identity genes. Mice were genetically engineered to inactivate BRG1 specifically in the endometrial epithelium. Endometrial glands were observed embedded in uterine myometrium, indicating adenomyosis-like phenotypes. Molecular similarities were observed between BRG1 and ARID1A mutant endometrial cells in vivo, including loss of epithelial cell adhesion and junction genes. Collectively, these studies illustrate overlapping contributions of multiple SWI/SNF subunit mutations in the translocation of endometrium to distal sites, with loss of cell integrity being a common feature in SWI/SNF mutant endometrial epithelia. Graphical Abstract: